A Few Factors of Creation of The New Polymer Enterprises - Alexey Georgievich KORYAKOV; Mariya Vladimirovna ZAKHAROVA; Martinas PRAZAUSKAS (Communications of International Proceedings, 2021)
The article discusses an approach to the creation of new chemical industries in the field of polymer materials. An assessment of the stages of the formation of polymer industries is provided and a three-dimensional model of the conditions for their creation is developed.
Keywords: chemical industry; polymer production; phase of the macroeconomic cycle.